THE DEVELOPMENT AND USE OF COMPETENCE-BASED APPROACH TO FUND OF ASSESSMENT TOOLS WITHIN THE FRAMEWORK OF THE INTERMEDIATE EVALUATION OF AN ACADEMIC SUBJECT - Yelena K. Gitman; Mikhail B. Gitman; Valeriy Yu. Stolbov; Irina D. Stolbova (Высшее образование в России)
Recommendations on formation and implementation of Fund of Assessment Tools (FAT) to control the level ofprogress in an academic subject in intermediate certification stages for bachelor, specialist and master programs are suggested. The proposed structure of FAT, recommended indicators and assessment criteria allow to assess more objectively disciplinary parts and competency components.